Upaya Guru Bimbingan dan Konseling dalam Mengatasi Perilaku Murid yang Melanggar Tata Tertib di SMPN 1 Rao Selatan - Purnia, Poppy; Syawaluddin, Syawaluddin (TSAQOFAH, 2023)
This article was created with the aim of knowing what factors influence student behavior, what efforts are made by the guidance counselor in overcoming them, and what are the supporting and inhibiting factors in dealing with behavior violating student rules. The supporting factors for the guidance counselor in overcoming the behavior of SMPN 1 Rao Selatan students are cooperation between teachers, the existence of a habitutation program carried out at school, collaboration with parents of students, and motivation from students. Whil the inhibiting factors for the counseling teacher in overcoming behavior violating the rules are parents, association outside of school, and the lack of awareness of the students themselves.